OpenVPN Server Menggunakan Ubuntu Server 20.04 LTS pada Amazon Web Services - Cilvia Chairunnisa; Indri Rahmayuni; Deddy Prayama (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
Computer network is a technology that is widely used by companies that functions to connect one location to another. The use of the internet as a communication medium is not only very beneficial for the company, but still has weaknesses in terms of security. The obstacles faced are how to access data in the office and turn employee devices into a network required for API testing without having to come directly to the office, of course with a very adequate level of security. The solution that can be used for this problem is to build an OpenVPN server as a tunnel to be applied to help employees access the office network or other employees. By implementing the system, testing the API on mobile applications, which runs on the local office computer or runs on client computers or other employees